RANCANG BANGUN REKAM MEDIS ELEKTRONIK PELAYANAN RAWAT JALAN BERBASIS WEB - Amaliyah, Hikmah; Yunus, Muhammad; Roziqin, Muhammad Choirur; Pratama, Mudafiq Riyan (Politeknik Negeri Jember, 2024)
Patrang Health Center as a health facility that organizes medical records in supporting the provision of individual health services is carried out semi-manually and hasn’t implemented SIMPUS where the recording is still performed manually and assisted by using Google Sheet. The average number of daily visits that aren’t comparable to the staff available and haven’t optimized technology has hampered the process of providing medical records so it can affect the quality of service. This requires a system that can support the implementation of medical records so it can optimize the staff in providing outpatient services. This study aims to built an electronic medical record of outpatient services at the Patrang Health Center by using the R&D as a research type and using the Waterfall as a system development method which includes the phases of defining requirements, design system, implementation and testing the system using the Black Box testing method where the menus and functions are in accordance with user requirements and run successfully. The system has a menu to record registration activities, examinations, medicine data management and making reports so that it can improve the quality of officers in providing services.